Analisis Nilai Pendidikan Ibadah dalam Kitab Qomi’ut Thughyan ‘ala Syarhi Syu’bul Iman Karya Syekh Muhammad Nawawi bin Umar al-Jawi al-Bantani dan Aktualisasinya pada Konteks Pendidikan Islam Modern - Muhammad Fodhil; Risqi Maulidatul Charisya (ANWARUL, 2025)
The lack of internalization of worship values in contemporary Islamic education often delivered in a normative and decontextualized manner poses a major challenge to the development of students’ spiritual character. This study aims to analyze the educational values of ‘ibadah (worship) found in Qomi’ut Thughyan ‘Ala Syarhi Syu‘bul Iman by Shaykh Muhammad Nawawi bin Umar al-Jawi al-Bantani, and to examine their relevance and actualization in the context of modern Islamic education. A qualitative approach was employed using the library research method, with the classical text serving as the primary source and academic literature as secondary references. The findings reveal that the book outlines core ‘ibadah values, including purification, the five daily prayers, almsgiving (zakat), fasting, i’tikaf, and pilgrimage (hajj), alongside a strong emphasis on discipline in worship. These values are not merely ritualistic but encompass profound moral and spiritual dimensions that contribute to shaping students into religious, responsible, and socially aware individuals. The study concludes that Qomi’ut Thughyan presents transformative and contextual principles of worship education, making it a valuable reference for developing a holistic Islamic education system. The implication is that educators must adapt the worship values from this classical work into contextual and practical teaching strategies to ensure that Islamic education remains spiritually grounded and pedagogically relevant.